THE SCOPE OF FUNCTIONS AND STRENGHT OF INSTITUTIONS IN ECONOMIC POLICY OF THE EU MEMBER STATES FROM CENTRAL AND EASTERN EUROPE. CONCEPTION OF ANALYSIS - Jaźwiński, Ireneusz (Ekonomika, 2011)
The manner of conducting economic policy determines various phenomena and socio-economic processes, including economic development and growth, to a considerable degree. A significant role in economic and social sciences is attributed to international comparative studies. The aim of the study was introduction of the conception for analysis of the scope of functions and strength of institutions on an example of the national policies of the EU member states from Central and Eastern Europe. The paper introduces the selected dimensions of economic policy in the EU member states from Central and Eastern Europe. On the basis of the use of existing indices, the measures of these dimensions are proposed. Also, elements of the typology of economic policies of these countries considering the selected policy dimensions are presented. The analyses show that there are differences among national economic policies of particular states of Central and Eastern Europe. From the standpoint of economic policy and its dimensions, the situation is most favourable in countries with the most powerful institutions: the Czech Republic and Estonia. It is crucial to strive after improvement of the quality of institutions in individual states, which should result in a faster socioeconomic development and an increased efficiency of the public authorities.